Public Service-Based Community: Study Case Integrated Health Service for Elderly in an Indonesian Village Level - Solicha, Fira Arma Atus; Choiriyah, Ilmi Usrotin (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This study aims to analyze the role of Posyandu Elderly cadres in improving the quality of life of the elderly in Jambangan Village, with a focus on education, information dissemination, assistance, and health monitoring. This research is important because the quality of life of the elderly is greatly influenced by the health services they receive. Good support from Posyandu cadres can help the elderly maintain their health and well-being, and overcome barriers to health services in the community. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis techniques include data collection, data reduction, conclusion/verification, and data presentation. The results showed that the role of cadres in education had gone well, but the face-to-face lecture method tended to be monotonous and less interesting, so that some elderly people had difficulty understanding the material. Information dissemination also faces challenges in reaching all elderly people, and sometimes there is miscommunication between cadres and midwives. In health assistance, the limited number of cadres has an impact on suboptimal data recording. Meanwhile, health monitoring has been done well through home visits, but the manual reporting system and lack of technology utilization hamper efficiency.